Resurgence of superconductivity and the role of dxy hole band in FeSe1−x Te x - Archie B. Morfoot; Timur K. Kim; Matthew D. Watson; Amir A. Haghighirad; Shiv J. Singh; Nick Bultinck; Amalia I. Coldea (Communications Physics, 2023)
Abstract Iron-chalcogenide superconductors display rich phenomena caused by orbital-dependent band shifts and electronic correlations. Additionally, they are potential candidates for topological superconductivity due to the band inversion between the Fe d bands and the chalcogen p z band. Here we present a detailed study of the electronic structure of the nematic superconductors FeSe1−x Te x (0 < x < 0.4) using angle-resolved photoemission spectroscopy to understand the role of orbital-dependent band shifts, electronic correlations and the chalcogen band. We assess the changes in the effective masses using a three-band low energy model, and the band renormalization via comparison with DFT band structure calculations. The effective masses decrease for all three-hole bands inside the nematic phase, followed by a strong increase for the band with d x y orbital character. Interestingly, this nearly-flat d x y band becomes more correlated as it shifts towards the Fermi level with increasing Te concentrations and as the second superconducting dome emerges. Our findings suggests that the d x y hole band, which is very sensitive to the chalcogen height, could be involved in promoting an additional pairing channel and increasing the density of states to stabilize the second superconducting dome in FeSe1−x Te x . This simultaneous shift of the d x y hole band and enhanced superconductivity is in contrast with FeSe1−x S x .